2006
DOI: 10.1111/j.1574-6968.2006.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct DNA repair pathways involving RecA and nonhomologous end joining in Mycobacterium smegmatis

Abstract: Mycobacterium smegmatis was used to study the relationship between DNA repair processes involving RecA and nonhomologous end joining (NHEJ). The effect of gene deletions in recA and/or in two genes involved in NHEJ (ku and ligD) was tested on the ability of bacteria to join breaks in plasmids transformed into them and in their response to chemicals that damage DNA. The results provide in vivo evidence that only NHEJ is required for the repair of noncompatible DNA ends. By contrast, the response of mycobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…qRT-PCR analysis of all accD members in M. tuberculosis and M. smegmatis showed that the three accD genes highly expressed and regulated during mycolate biosynthesis in pathogenic mycobacteria were (11,12,13,20,29,30). In contrast to procedures based on delivery vectors harboring a thermosensitive origin of replication (25,56), this method does not require growth temperature shifts (54).…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR analysis of all accD members in M. tuberculosis and M. smegmatis showed that the three accD genes highly expressed and regulated during mycolate biosynthesis in pathogenic mycobacteria were (11,12,13,20,29,30). In contrast to procedures based on delivery vectors harboring a thermosensitive origin of replication (25,56), this method does not require growth temperature shifts (54).…”
Section: Discussionmentioning
confidence: 99%
“…NHEJ-deficient M. smegmatis strains used in this work were as previously described by Korycka-Machala et al (5).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Following strategies reported previously that deleted DNA ligase genes in M. smegmatis (12), a suicidal recombination delivery vector was constructed to perform unmarked deletions in the ligA gene (MSMEG2361) of M. smegmatis. The vector carried the 5Ј end of ligA (68 bp) with the upstream region amplified with primers A-GR1 and A-GR2 (Table 2) connected to the 3Ј end of the gene (936 bp) and with the downstream region amplified with A-GR3 and A-GR4 primers ( (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…A two-step recombination protocol (12,17) was used to obtain single-crossover (SCO) strains carrying wild-type (wt) and disrupted ligA (⌬ligA) at its native locus on the chromosome. Using the strategy outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%